Aortic Coarctation Associated With Hypertrophic Cardiomyopathy in a Woman With Hypertension and Syncope: A Case Report With 8-Year Follow-Up - Yang, Hong; Wang, Hong; Li, Zongzhe; Yan, Jiangtao; Song, Yu-E; Zeng, Hesong; He, Xingwei; Li, Rui; Wang, Dao Wen (Frontiers in Cardiovascular Medicine, 2022)
Background: Coarctation of the aorta (CoA) is a common congenital cardiovascular malformation with aortic narrowing in the region of the ligamentum arteriosum. Hypertrophic cardiomyopathy (HCM) is a primary cardiomyopathy that is characterized by left ventricular wall thickening and likely left ventricular outflow tract (LVOT) obstruction. They are two irrelevant diseases and their coexistence has not been reported before. We described here a young female patient with CoA and HCM concurrently. Case presentation: The patient had hypertension since 18-years old and complained chest discomfort on effort and fatigue thereafter. She was diagnosed initially as hypertrophic cardiomyopathy and primary hypertension. The presence of CoA was not found until she was 35-years old when she had the onset of paroxysmal supraventricular tachycardia (PSVT) and presented with syncope. Failure of the ablation procedure via femoral artery revealed the possibilities of CoA and PDA that was confirmed by aortic CTA and angiography. CoA was treated then successfully by a covered stent and the patient’s symptoms improved remarkably. Additionally, the patient had typical imaging features of HCM and two novel HCM-causing heterozygous mutations were identified by genetic testing, DSP encoding desmoplakin and MYBPC3 encoding myosin-binding protein C. The HCM was suspected that might contribute to the patients’ clinical presentations and challenged the timely diagnosis of CoA. The 8-years follow-up aortic CTA and angiography revealed no stent-graft related complications. Moreover, no changes of HCM-related imaging features were found in the follow-up echocardiography 8 years after correction of aortic coarctation, which strengthened the diagnosis of HCM. Conclusion: We reported here the diagnostic challenges, management and 8-yeasr follow-up findings in a rare case of CoA combined with HCM. The case highlighted the importance for physicians to exclude CoA in young hypertensive patients, and proved the efficacy of stent repair in treating CoA in older patients.